Behavior of the geotextile reinforced dykes on sand-overlying-clay deposit - Yang, Shuaidong; Liao, Wei; Wang, Xiaoliang; Zhou, Mi; Zhang, Xihong; Zhuang, Shengzhen (Frontiers in Marine Science, 2023)
An extensive investigation on the performance of large geotextile mat dykes on stiff-over-soft soil deposits is carried out undertaken through numerical simulation in this paper. The large mat is reinforced by geotextiles with a new type of arrangement, i.e. non-uniform geotextile reinforcement. The numerical model is validated against centrifuge test data and other previously testing results, prior to conduct parametric study. It is found that large geotextile reinforced dykes on sand overlying clay fails through a global mechanism that the whole dam sank downwards together. It is found that the thickness of the sand layer, the width of the dyke base, and the shear strength of soft clay are the key influence factors on the stability of the dyke. A design flow chart is then proposed to quantity the performance of the geotextile mat dyke with non-uniform reinforcement, in terms of predicting allowable dyke fill height and the corresponding safety factor, which can be employed to provide refer for its design and construction.